PENDAHULU DARI PERILAKU MENDAUR ULANG RUMAH TANGGA - Dian Permatasari; B.M Purwanto (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2014)
Theory of Planned Behavior (TPB) is a basic theory which is commonly used in developing psychological and normative model. TPB provides a theoretical framework used to investigate the factors that underlie someone to do something, including recycling. Recycling is regarded as altruistic behavior, because someone’s decision to recycle is caused of awareness of the consequences of recycling behavior and ascription to responsibility toward the emergence of those consequences. However, some researchers also revealed that while recycling is an altruistic behavior, yet the goal of someone conducts the environmentally conscious behavior is not solely based on altruistic goal, but also based on egoistic goal. Sometimes, someone does recycling because the behavior is seen as an opportunity to get reward and or avoid the punishment.This study aims to determine the factors which are influencing household to recycle. To determine those factors, researcher develops Model of Household Recycling Behavior (MHRB) in order to create more comprehensive and integrated model of recycling. The survey was conducted of 385 households living in DKI Jakarta and Salatiga Town. The collected questionnaires are 355 questionnaires, but only 328 questionnaires that could be processed. Analysis of data uses SEM estimation with Maximum Likelihood technique.The results indicated that recycling attitude, concern for the community , moral norm, situational factor, and incetive did not influence household to recycle. Furthermore, the result indicated that perceived usefulness did positively influence recycling attitude. Finally, the results also indicated that subjective norm, self-efficacy, and past recycling behavior had positive influence on household recycling behavior.